Spatial Analysis of Flood Inundation From Sentinel-1 Imagery Using Google Earth Engine (Case Study: Bengawan Jero Lamongan Regency) - Irbah, Nafisatus Sania; Jaelani , Lalu Muhamad (GEOID, 2024)
Flooding is a natural disaster due to rivers that are no longer able to accommodate excessive rainwater so that water overflows and inundates the surrounding area. During the rainy season, many areas in Indonesia experience flooding, one of which is the Lamongan Regency. In early 2022, seasonal flooding occurred due to runoff from Bengawan Jero which caused many houses, agricultural land and access roads to be submerged in water. To improve disaster mitigation activities, it is necessary to identify flooding areas using remote sensing. The distribution area of flood inundation was identified using change detection and threshold methods. The change detection method is carried out by using ratio images from Sentinel-1 image data. The results of land cover in Lamongan Regency resulted in 9 land cover classes. Where is dominated by agricultural class land cover with an area of 1057.94 km2 with a percentage of the total area of Lamongan Regency is 60.53%. While the smallest land cover area is the mangrove class covering an area of 101.237 km2 with a percentage of the total area of 0.058%. Extraction of the inundation area was carried out with two different threshold values obtained from equations and statistical calculations. The flood inundation area generated on January 31, 2022, for the first threshold value is 54.932 km2 with an overall accuracy of 97% with a kappa coefficient is 0.94. While the flood inundation area with the second threshold value is 90.330 km2 with an overall accuracy of 94% and a kappa coefficient is 0.88.